Pemanfaatan Limbah Gula untuk Pembuatan Bioethanol yang dipengaruhi oleh Komposisi Khamir pada Proses Fermentasi - Sinar Perbawani Abrina Anggraini; Susy Yuniningsih (Universitas Tribhuwana Tunggadewi Malang, 2020)
The increasing needs of people who are not balanced with fuel supplies at the national and world level are bringing about the impact of the energy crisis. The reliance only on renewable energy makes people have to look for alternative energy sources. Bioethanol is a type of fuel that can replace fuel. The bioethanol process is fermented from biomass material with the help of microorganisms. This study aims to know the performance of yeast composition in the fermentation process against ethanol quality. The ingredients used are molasses with a sugar content of 54% as much as 8 L. Molasses is mixed with NPK, Urea, and the yeast Saccharomyces Cerevisiae. Khamir's composition varies by 8, 12, 16, 20, 24, 28, and 32 grams. To test ethanol levels on each variable by measuring the difference in water density and ethanol using a pycnometer. This study's result is the highest ethanol quality obtained at a sugar concentration of 12 grams (0.2%), at 5.6%. The lowest ethanol quality is obtained at a sugar concentration of 32 grams (0.4%) i.e., 3.29%, while in yeast composition 8, 16, 20, 24, 28 grams of ethanol quality continued to decrease consecutively to 3.6%, 5.4%, 5.3%, 5.2%, and 5.1%.